The Medan Suicide Attack : Enablers of Radicalism - Rahmah, Unaesah (2020)
A recent suicide bombing at the police headquarters in Medan, North Sumatra, was the first attack in Indonesia by a pro-IS cell since the death of the so-called “caliph” Abu Bakr al-Baghdadi. The radicalisation pathway of the suicide bomber underlines the role of religious study sessions, as against online radicalisation, and kinship influences within the pro-IS circle.